A New Method for Dimensioning and Designing the Zero-Sequence Electromagnetic Filter Considering System Displacement Power Factor - Fonseca Buzo, Ricardo [UNESP]; Oliveira, Luis Carlos Origa de [UNESP]; Leao, Fabio Bertequini [UNESP] (Ieee-inst Electrical Electronics Engineers Inc, 2020)
This paper proposes an innovative method for dimensioning and designing the zero-sequence electromagnetic filter applied to three-phase four-wire distribution power systems. As premises, the optimum ratio between zero-sequence and positive-sequence impedances of the filter must be established in order to potentiate the filtering percentage of zero-sequence currents and ensure the quality of the supply system displacement power factor. The calculations are based on the sequential harmonic transmittances of the equivalent circuit reduced to the coupling point of the electromagnetic filter. To validate the proposed method, the results obtained with the application of the electromagnetic filter designed in a test system using the MATLAB software are compared to the results of the system modeled in the PSIM software.
Keywords: Legged locomotion; Coils; Inductance; Power harmonic filters; Resistance; Electromagnetics; Magnetic flux; Mitigation; zero-sequence; dimensioning; designing; electromagnetic filter